SISTEM PAKAR DIANOGSIS KERUSAKAN CABLE FIBER TO THE HOME DENGAN METODE FORWARD CHAINING - Hamonangan, Evander; Suharyanto, Cosmas Eko (LPPM Universitas Putera Batam, 2021)
The development of telecommunications technology as a communication has grown rapidly. In the rapid development of telecommunications, a transmission media facility is needed that is capable of transmitting information with large capacities and capable data transfer speeds. One of the transmission media that has been used is optical fiber in a telecommunications system called JARKOLAF (Fiber Access Local Network). The development of JARKOLAF used is FTTH (Fiber To The Home) which often experiences an increase in attenuation caused by bad weather conditions. Based on the problems above, it is necessary to diagnose the damage using the forward chaining method.